Advertisement call of the leptodactylid frog Preceratophys avelinoi - Kwet, Axel (2003)
The Proceratophrys bigibbosa species group has recently been reviewed by Kwet and Faivovich (2001). Proceratophrys cristinaeBraun, 1973 was regarded as a juniorsynonym of Proceratophrys bigibbosa (Peters, 1872), whereas the species identi ed as P. bigibbosa by Braun (1973) was described as Proceratophrys brauni Kwet and Faivovich, 2001. In addition to P. bigibbosa and P. brauni, two more species belong to the bigibbosa group, Proceratophryspalustris Giaretta and Sazima, 1993 and Proceratophrysavelinoi Mercadal de Barrio and Barrio, 1993.